2020
DOI: 10.1186/s12998-020-00349-y
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of kinesiology taping on pain, functional disability and lumbar proprioception in individuals with nonspecific chronic low back pain: a double-blinded, randomized trial

Abstract: Background This study aimed to evaluate the effect of kinesiology taping (KT) on lumbar proprioception, pain, and functional disability in individuals with nonspecific chronic low back pain (CLBP). Methods Thirty individuals with nonspecific CLBP participated in this double-blinded, randomized clinical trial from July 2017 to September 2018. The participants were randomized into two groups: KT (n = 15) and placebo group (n = 15). KT was applied wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…It usually occurs between the fifth and seventh months of pregnancy, and in some cases, pregnancy pain in the lower back can begin as early as eight to 12 weeks into the pregnancy. Women who have lower back problems before pregnancy are at higher risk for lower back pain, which can start early in pregnancy [ 33 , 34 ]. A follow-up survey of 1131 pregnant women in the United States found that 0.4% of low back pain occurred in early pregnancy, 24.4% in the second trimester, and 75.1% in the third trimester.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It usually occurs between the fifth and seventh months of pregnancy, and in some cases, pregnancy pain in the lower back can begin as early as eight to 12 weeks into the pregnancy. Women who have lower back problems before pregnancy are at higher risk for lower back pain, which can start early in pregnancy [ 33 , 34 ]. A follow-up survey of 1131 pregnant women in the United States found that 0.4% of low back pain occurred in early pregnancy, 24.4% in the second trimester, and 75.1% in the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of KT may not be completely clear, but as physical therapy, KT is widely used in the clinic. In recent years, clinical attention has been paid to the effect of KT on low back pain during pregnancy, and relevant studies have been published, showing that KT has a significant effect on low back pain during pregnancy [ 27 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It usually occurs between the fth and seventh months of pregnancy, and in some cases, pregnancy pain in the lower back can begin as early as eight to 12 weeks into the pregnancy. Women who have lower back problems before pregnancy are at higher risk for lower back pain, which can start early in pregnancy [31,32]. A follow-up survey of 1131 pregnant women in the United States found that 0.4% of low back pain occurred in early pregnancy, 24.4% in the second trimester, and 75.1% in the third trimester.…”
Section: Discussionmentioning
confidence: 99%
“…(9) One study done by Soheila Abbasi from Iran concluded that Kinesiotape can decrease pain and disability scores in individuals with nonspecific chronic low back pain after 3 days of kinesiotape application. (10) So, there is conflict in literature about immediate effect of kinesiotape for relieving pain.…”
Section: Discussionmentioning
confidence: 99%